2020
DOI: 10.3390/cancers12071904
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus 16 E7 Promotes EGFR/PI3K/AKT1/NRF2 Signaling Pathway Contributing to PIR/NF-κB Activation in Oral Cancer Cells

Abstract: A subset of oral carcinomas is etiologically related to high-risk human papillomavirus (HR-HPV) infection, with HPV16 being the most frequent HR-HPV type found in these carcinomas. The oncogenic role of HR-HPV is strongly dependent on the overexpression of E6 and E7 oncoproteins, which, in turn, induce p53 and pRb degradation, respectively. Additionally, it has been suggested that HR-HPV oncoproteins are involved in the regulation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Furthermore, both epidermal growth factor receptor/mitogen-activated protein kinase kinase/extracellular signal-regulated kinase (EGFR/MEK/ERK) and phosphoinositide 3-kinase/protein kinase B (PI3K/AKT) pathways may be involved in the activation of Pirin by HPV-E7 oncoprotein in oral cells [63], which is in line with a previous report on transformed rat fibroblasts [93]. More recently, we demonstrated that EGFR/PI3K/AKT1/NRF2 signaling promotes Pirindependent canonical NF-κB activation, which, in turn, promotes oral cell migration [37]. Altogether, this strongly suggests a novel carcinogenic mechanism by which Pirin is involved in oral cancer, although the clinical consequences remain to be determined.…”
Section: Head and Neck And Gastrointestinal Cancerssupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, both epidermal growth factor receptor/mitogen-activated protein kinase kinase/extracellular signal-regulated kinase (EGFR/MEK/ERK) and phosphoinositide 3-kinase/protein kinase B (PI3K/AKT) pathways may be involved in the activation of Pirin by HPV-E7 oncoprotein in oral cells [63], which is in line with a previous report on transformed rat fibroblasts [93]. More recently, we demonstrated that EGFR/PI3K/AKT1/NRF2 signaling promotes Pirindependent canonical NF-κB activation, which, in turn, promotes oral cell migration [37]. Altogether, this strongly suggests a novel carcinogenic mechanism by which Pirin is involved in oral cancer, although the clinical consequences remain to be determined.…”
Section: Head and Neck And Gastrointestinal Cancerssupporting
confidence: 91%
“…ABL2 is a cytoplasmic tyrosine kinase which coordinates actin remodeling through tyrosine phosphorylation of proteins controlling cytoskeleton dynamics. Taken together, the functional association of Pirin with proteins involved in cytoskeleton reorganization partially explains the link between Pirin overexpression and increased cell migration in some cellular models [37,38]. Further experimental settings are warranted to elucidate the molecular mechanisms involved in these functional associations.…”
Section: Pirin Structure and Biological Functionsmentioning
confidence: 90%
See 1 more Smart Citation
“…Likewise, it was observed that PIR is upregulated by HR-HPV E7 oncoprotein dependent on EGFR/MEK/ERK and PI3K/Akt signaling pathways. Subsequently, Pirin protein induces NF-κB activation and is involved in EMT and migration in HPV-positive cervical cancer cells [158]. Taken together, these data indicate that PIR may be important in both TS and HPV-mediated carcinogenesis.…”
Section: Tobacco Smoke Alters Cellular Gene Expression Involved In Hpmentioning
confidence: 73%
“…It is worthy of note however that HPV infection and tobacco smoking interacted with each other, tobacco exposure enhancing HPV16-E6 and -E7 oncogene transcription (36) and overexpression of HPV 16-E7 oncoprotein contributing to oral cancer progression (37). These interactions could be modulated according to time of oral HPV infection and life course smoking trajectories which could modify the HNC risk (38).…”
Section: Discussionmentioning
confidence: 99%